Cerner Millennium™: The Innsbruck Experience - Lechleitner, G.; Pfeiffer, K.-P.; Wilhelmy, I.; Ball, M. (Methods of Information in Medicine, 2003)
Objectives: A Clinical Information System, serving more than 2,000 users was to be implemented at three hospitals of TILAK (Tiroler Landeskrankenanstalten GmbH), including the University Hospital of Innsbruck. The system was intended to integrate data from radiology, laboratory, and pathology subsystems with patient data.Methods: Using Cerner Millennium™ software and Health Level 7 standards, the first stage of an Electronic Patient Record (EPR) was built. Direct data entry was facilitated using either a Microsoft Word text processor (with subsequent authentication workflow) or structured forms. An enterprise-wide scheduling module allows coordination and storage of patient appointments directly in the EPR. As required by security policy, the Cerner software regulates the varying degrees of information exchange among organizations and departments within the enterprise.Results: First experiences indicate satisfactory acceptance of system functionalities. The introduction of Cerner Millennium at TILAK has achieved essential goals defined at the beginning of the project. Basic functionalities – free text documentation, standardized documentation, scheduling, and some parts of order entry – are offered in a user friendly manner. Integration with existing systems to complete the EPR has been successful using standard interfaces (HL7).Conclusion: TILAK concluded that it was possible to successfully implement a Clinical Information System (CIS) developed mainly for the American market in a European healthcare environment. Some adaptations and functional extensions were necessary (e.g., the discharge summary “Arztbrief”). The system had enough flexibility to meet the requirements and specifications of European healthcare processes. A key factor of success was the establishment of a basic level of understanding and communication between the software vendor and the TILAK user community.
Keywords: Hospital information systems; clinical information systems; implementation strategy; case studies; electronic patient record